Non-economic loss and damage: addressing the forgotten side of climate change impacts - Olivia Serdeczny; Eleanor Waters; Sander Chan (Deutsches Institut für Entwicklungspolitik (DIE), 2016)
Non-economic loss and damage (NELD) has emerged as a new concept in the negotiations under the United Nations Framework Convention on Climate Change (UNFCCC). It refers to the negative impacts of climate change that are difficult to measure or quantify. The value of NELD cannot easily be expressed in monetary terms, which has left them mostly neglected in climate-risk and cost estimates. As a result, although NELD are vital to those affected, they often go unnoticed by the outside world. A focus on NELD invites engagement with the normative dimensions of the loss-and-damage debate: Whose losses and damages count and how are they counted? What losses are the global community willing to accept as a result of unmitigated climate change? At the same time, the practical aspects of NELD need to be considered: What tools and instruments are available to avoid NELD? What are appropriate ways to react to NELD that prove to be unavoidable or that have already occurred? Instances of NELD are highly diverse. Relevant insights can be gained from a range of academic disciplines, including economics, human geography and environmental psychology. Still, few studies explicitly address NELD. Currently, 10 meta-categories of NELD can be identified: Human Life, Meaningful Places, Cultural Artefacts, Biodiversity, Ecosystem Services, Communal Sites, Production Sites, Intrinsic Values, Identity and Agency. The diversity of NELD can be better understood through a focus on their main characteristics: context-dependence and incommensurability of value. Both attributes pose challenges to policy-making. Context-dependence is particularly problematic in an international setting in which actors will likely need to rely on universal standards for the recognition of losses. Incommensurability means that values cannot be ex-pressed through the use of a common unit. This renders monetary assessments as a means of valuation problematic. Monetisation may provide useful information for cost-benefit analyses of mitigation or adaptation scenarios, but it is less insightful in terms of how to avoid NELD or respond to them once they have occurred. Such conceptual clarity is key for the integration of available knowledge and the identification of effective approaches to NELD. In order to avoid NELD at the national level, they need to be included in risk- and vulnerability assessments. Assessments need to include negative side-effects of mitigation and adaptation and be conducted in a decentralised and participatory manner. Efforts should be made to share findings with the wider public, nationally and inter-nationally. Addressing NELD at the international level should rely on agreed assessment rules for the recognition of NELD rather than a static set of items. The universality of standards needed for an international framework would thus shift from indicators to a process-based scheme of assessment rules under the UNFCCC. These should inform measures that avoid as well as those that react to NELD. The emergence of NELD in the context of the UNFCCC provides an excellent opportunity to raise awareness of an oft-ignored dimension of climate impacts. An orchestrated integration of research findings from a broad range of disciplines is needed to provide a solid evidence-base for designing just and effective approaches to address NELD.
Keywords: 330; Klimawandel; Demokratie und Autokratie